Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.celrep.2017.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Axonal Bouton Dynamics following Visual Deprivation In Vivo

Abstract: SummaryPersistent synapses are thought to underpin the storage of sensory experience, yet little is known about their structural plasticity in vivo. We investigated how persistent presynaptic structures respond to the loss of primary sensory input. Using in vivo two-photon (2P) imaging, we measured fluctuations in the size of excitatory axonal boutons in L2/3 of adult mouse visual cortex after monocular enucleation. The average size of boutons did not change after deprivation, but the range of bouton sizes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
(64 reference statements)
2
14
0
Order By: Relevance
“…This diversity is manifested in the broad distri-butions of many functional and morphological properties, such as postsynaptic current amplitude, dendritic spine volume and postsynaptic density (PSD) area. Such distributions are not only broad but also rightward skewed and heavy-tailed, and are often described as log-normal (Murthy et al, 1997;Song et al, 2005;Arellano et al, 2007;Lefort et al, 2009;Minerbi et al, 2009;Loewenstein et al, 2011;Ikegaya et al, 2013;Keck et al, 2013;Statman et al, 2014;Cossell et al, 2015;Zhang et al, 2015;Hobbiss et al, 2018;Ishii et al, 2018;Masch et al, 2018;Sakamoto et al, 2018;Sammons et al, 2018;Wegner et al, 2018;Santuy et al, 2018; for review, see Barbour et al, 2007;Buzsáki and Mizuseki, 2014;Scheler, 2017). Such distributions, reflecting of a majority of weak/small synapses and a diminishing tail of increasingly stronger/larger synapses, were suggested to optimize storage capacity, neuronal firing rates and long-distance information transfer and thus impart important properties to neuronal networks (Song et al, 2005;Barbour et al, 2007;Lefort et al, 2009;Ikegaya et al, 2013;Buzsáki and Mizuseki, 2014;Scheler, 2017;Humble et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This diversity is manifested in the broad distri-butions of many functional and morphological properties, such as postsynaptic current amplitude, dendritic spine volume and postsynaptic density (PSD) area. Such distributions are not only broad but also rightward skewed and heavy-tailed, and are often described as log-normal (Murthy et al, 1997;Song et al, 2005;Arellano et al, 2007;Lefort et al, 2009;Minerbi et al, 2009;Loewenstein et al, 2011;Ikegaya et al, 2013;Keck et al, 2013;Statman et al, 2014;Cossell et al, 2015;Zhang et al, 2015;Hobbiss et al, 2018;Ishii et al, 2018;Masch et al, 2018;Sakamoto et al, 2018;Sammons et al, 2018;Wegner et al, 2018;Santuy et al, 2018; for review, see Barbour et al, 2007;Buzsáki and Mizuseki, 2014;Scheler, 2017). Such distributions, reflecting of a majority of weak/small synapses and a diminishing tail of increasingly stronger/larger synapses, were suggested to optimize storage capacity, neuronal firing rates and long-distance information transfer and thus impart important properties to neuronal networks (Song et al, 2005;Barbour et al, 2007;Lefort et al, 2009;Ikegaya et al, 2013;Buzsáki and Mizuseki, 2014;Scheler, 2017;Humble et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In order to study whether there were also changes in the output of GAD67‐EGFP neurons, we quantified the density of en passant boutons in EGFP expressing axons in the layer I of V1 (Figure a,b), the major projection field of these interneuronal subpopulation. Moreover, we quantified the size and fluorescence intensity (which is directly related to the size) of axonal boutons, structural readouts of cortical reorganization by experience‐dependent plasticity (Sammons, Clopath, & Barnes, ). No significant differences were found when comparing the deprived animals with their controls regarding the density of axonal boutons (Figure c; p = .657).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with those of other studies. 23 Sammons et al 8 found that LTP and long-term depression were higher in deprived versus control cortexes, indicating that MD increases plasticity in the deprived cortex. Furthermore, LTP was increased in the contralateral visual cortex by 76% after MD in cPKCγ +/+ mice but increased by only 32% in cPKCγ −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Similar studies using P17 mice have shown that MD strengthens excitatory synaptic connections of layer 4 7 and induces plasticity in layers 2 and 3 of the deprived cortex. 8 However, some studies have shown that, after MD, miniature inhibitory postsynaptic currents (IPSCs) and the density of postsynaptic GABA A receptors were increased in layer 4 of the visual cortex, 9 indicating that the plasticity of the visual cortex was decreased after MD. Thus, how visual cortex plasticity changes after MD is incompletely understood.…”
mentioning
confidence: 99%